The Influence of Recurrent Modes of Climate Variability on Intensity and Temporal Phase of Local Hydroclimatic Variation in South Carolina - Lee, Donghyun (Journal of Hydrological Ecology and Water Security, 2025)
Understanding how large-scale climate circulation influences hydroclimatic factors in both tropical and extratropical regions is crucial. This study employed empirical methods to identify areas with consistent hydroclimatic signals associated with the El Niño/Southern Oscillation (ENSO). We examined the climatic linkages between the warm and cold phases of ENSO and precipitation patterns across South Carolina. Spatial coherence values were calculated using monthly precipitation composites over a 2-year ENSO cycle, and candidate regions were identified using the first harmonic fit. Temporal consistency rates were determined through aggregate composites and index time series (ITS) to pinpoint core regions. This study identified three core regions: the Upstate Region (USR), the Pee-Dee Region (PDR), and the Lowcountry Region (LCR), with the LCR showing the most significant response to both warm and cold ENSO forcings. During ENSO warm (cold) years, precipitation composites showed above (below) normal levels in these regions from winter to spring. Spatial coherence rates for El Niño (La Niña) in USR, PDR, and LCR were between 0.96 and 0.98 (0.95 and 0.97), and temporal consistency rates ranged from 0.72 to 0.83 (0.73 to 0.77). Composite-harmonic analysis revealed that precipitation anomalies tend to reverse signs between opposite ENSO phases, with positive anomalies in warm years showing more coherence and stronger responses compared to negative anomalies in cold years. The findings indicate that South Carolina's precipitation patterns are significantly influenced by ENSO, highlighting a climatic teleconnection between large-scale climate circulation and middle latitude precipitation.